UJI EFEK PROTEKTIF MADU PADA JARINGAN DUODENUM TIKUS JANTAN GALUR WISTAR YANG DIBERI PAJANAN ASPIRIN - Agung Prasetyo Agung (Faculty of Medicine Universitas Mataram, 2022)
Background: Peptic ulcer is a damage to the mucosal layer generally in the stomach or duodenum. Aspirin is one of group called NSAIDs which cause peptic ulcer disease. Honey has antioxidant activity from (the) compounds contained in honey in the form of flavonoids and phenolic acids. Noor et al proved that honey can protect the body from the chemical toxic effects. Objective/aim: Determine the protective effect of honey on aspirin induced duodenal tissue of wistar rats. Methods: The design of this study was a randomized post test only control group. This study used 30 rats divided into 5 groups: normal control group (KN), treatment group M dose I (KP1) (1.55ml / kgBB),treatment group M dose II (KP2) (3.1 ml / kgBB), positive control group (K+) (sucralfate 4 ml / kgBB), and the negative control group (K-) (aspirin 400mg/kgBB). Honey was given orally for 7 days. One hour after administration of honey, rats were given aspirin 400 mg / kgBB. The rats were killed on the 8th day and the duodenal was taken for histopathology assessment. Data analysis used SPSS version 23.0 with Kruskal Wallis followed by Post Hoc Mann Whitney. Results: Lighter damage was obtained in the treatment group (KP1 and KP2) compared to the negative control group (K-) (p <0.050). Conclusion: Honey provides a protective effect on rat’s duodenal tissue given aspirin exposure.